The complementarity of community-based water and sanitation interventions: evidence from Mozambique - Melinda Vigh; Chris Elbers; Jan Willem Gunning (Tinbergen Institute, 2019)
We use data on a large-scale water and sanitation program in rural Mozambique, implemented between 2008 and 2013, to investigate the complementarities between a behavior-change-based community-led total sanitation intervention and a community water supply intervention. Our findings indicate that the sanitation intervention increased the adoption of handwashing with soap or ash by 11 percentage points, latrine ownership and use by 8 percentage points, and the use of improved water points by 15 percentage points (conditional on access). Combining the water supply and sanitation interventions increased the treatment effects on all three outcomes. However, we find that the effect on toilet ownership was in large part driven by the selective intervention allocation of the implementing NGOs. These effects are measured up to 4 years after the intervention.
Keywords: D04; I15; O12; 330; impact evaluation; sanitation; WASH; CLTS; correlated random effects